Macroeconomic, institutional and financial determinants of current account balances: A panel data assessment - Yasin Baris Altayligil; Murat Çetrez (Journal of Economic Structures, 2020)
This study aims to find out the fundamental macroeconomic, institutional and financial determinants of current account balances by using panel data analysis method. The analysis is carried out by using the data for the period between 1986 and 2013 of 97 developing and developed countries. We find that the determinants of current account balances can be related to the factors such as fiscal balance, growth, terms of trade, exchange rate, trade openness, stage of economic development, oil dependency, financial market development, macroeconomic stability and institutional quality. A rise in growth rate, real effective exchange rate, fiscal deficit, trade openness, institutional quality, financial market development and stage of development generates larger current account deficits. A rise in terms of trade, inflation rate (representing macroeconomic stability), crude oil export reduces the current account deficits. For industrial countries, macroeconomic stability and growth also have the opposite effect on current account balances compared with other groups. The legal system and property rights, voice and accountability, political stability and absence of violence, political risks are identified as the institutional determinants of current account balances.
Keywords: F14; C33; G20; K11; 330; Current account balances; Macroeconomic stability; Institutions; Financial development; Panel data